Synthesis, characterisation and application of quaternised pectin as flocculant in wastewater treatment. (20th May 2020) - Sin, Lem Khe; Yhaya, Mohd Firdaus Bin; Talebi, Amir; Ismail, Norli
Citrus pectin is modified by quaternisation and named with quaternised pectin (QP) to enhance the flocculating efficiency of pectin. QP was characterised by Fourier-transform infrared spectroscopy (FTIR), gel permeable chromatography (GPC) and zeta potential. The results of QP characterisation revealed that functional groups are hydroxyl, carboxyl and amino group, the molecular weight is 380, 188 Da, and zeta potential is in range of 24.68 to 33.95 mV. Jar test was used to evaluate the coagulation-flocculation properties of QP with the prior addition of ferric chloride as a coagulant. Three factors (pH, [FeCl3 ] (mg/L) and [QP] (mg/L)) were found essential for the removal of turbidity, suspended solids (SS), chemical oxygen demand (COD) and colour of anaerobic-aerobic treated palm oil mill effluent (AATPOME). Response surface methodology (RSM) was used for optimisation, and the results of central composite design (CCD) for the optimum conditions were pH 5, the dosage of FeCl3 at 927 mg/L, and the dosage of QP at 6.4 mg/L.